Paper Clay Game (Paper Paper) On Motorcycle Development Smoother Age 4 Until 5 Years In Dharma Women Tosaren II Kindergarten Kediri - Riza Tsalatsatul Mufida; Maria Oktaviani Abu (Journal for Quality in Women's Health, 2018)
One effort to improve fine motor skills is the game of pulp. The purpose of this research is to know the effect of pulp game on the development of fine motor development of children 4 to 5 years. This study uses the research method "Experimental Desaign" with type "One Group Pretest Posttest Desaign", population of 30 students in Tk Dharma Wanita Tosaren II Kecamatan Pesantren Kediri, using total sampling technique. The independent variable in this research is the pulp game, while the dependent variable is the smooth motor development of 4-5 years old child. Almost half of respondents, the level of fine motor development prior to the giving of the pulp game including the warning category of 12 people (40.0%). However, almost all respondents, the level of fine motor development after giving the game of pulp, including the normal category of 24 people (80.0%). Wilcoxon test results show value ρ value = 0.000 so that <α = 0.05, then H0 is rejected and H1 accepted then there is influence of pulp to the development of fine motor in children aged 4-5 years in kindergarten Dharma Wanita Tosaren II Kecantren Pesantren Kediri. Based on the result of this study it is expected taht the pulp game can be applied in helping improve the fine motor of the child